الملامح عن الأنشودة الإسلامية بماليزيا - Ahmad H.Osman, Rahmah; Tehhae, Ibrahim (Kolej Universiti Insaniah, 2010)
This study investigates an aspect of Islamic literature in the form of nashid (Islamic litanies, poems and songs. Arguments and criteria for what is considered Islamic literature is put forth and this art form is weighed against them. A case is presented for Nashid to be an acceptable form of Islamic art. Taking Malaysia as its study context, it examines the popularity and content of these Nashids and its appeal to both young and old. It is found to be a strong alternative to other forms of music. This form of Islamic art has done for Malaysia what the “mutun” have done for the Arab land in that children as well as adults remember and memorize them well and thus they are a great medium for Islamic education and a tool of Islamic awareness and values in the Malaysian context.